La gestión escolar a través de los sistemas de comunicación e información para los padres de familia de la unidad educativa once de noviembre en los quintos años paralelos a, c y d, en la ciudad de Latacunga en el año lectivo 2014-2015 - Flores Tello, María de Lourdes (2015)
This research is related to school management through parents focused on communication systems. It is based on social, psychological and educational impact’s importance. At the moment, the institution observed showed a strong weakness in a right communication process. Because, it reports just a basic way on situations and events happened with students and internal processes. For this reason, this project proposes communicating strategies on communication products design in order to improve school management. These strategies will be implemented in the fifth grade: "A", "C" and "D" at “Once de Noviembre” basic education school. This action helps to ease the difficulties and achieve a real feedback process that promotes an integral growth in actors in the educational process. For this research, techniques were used such as the survey and interviews. These techniques helped to demonstrate the incorrect way applied in past times which were identified in the situational analysis. For this reason, the proposal is a design on communication strategies’ manual. These strategies are a tool collection of that will be informed regarding educational processes was raised. These activities reaffirms that the educational community should be a permanent stage of continuous improvement in communication processes. It shows a successful autonomy and decision-making ability, to ensure quality education. So, it demonstrates its development, progress and innovation in educational management